1984
DOI: 10.1111/j.1476-5381.1984.tb10771.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphorothioate analogues of ATP, ADP and AMP on guinea‐pig taenia coli and urinary bladder

Abstract: 1Phosphorothioate analogues of ATP, ADP and AMP were tested on the guinea-pig taenia coli and urinary bladder. 2 The Rp diastereoisomers of the phosphorothioate analogues, ATP-ax-S and ADP-cx-S were respectively 7 and 3 times more effective than the Sp diastereoisomers in causing relaxation of the taenia coli. No stereoselectivity was observed for the diastereoisomers of ATP-3-S. 3 In guinea-pig bladder, no stereoselectivity was observed for any of the phosphorothioate analogues. 4 These results show that P2-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Fur-thermore no correlation has been reported between the rate of breakdown of an agonist and its pharmacological potency at P2Y receptors (Welford et al, 1986). ADP-fl-S has been shown to be more potent than ATP or ADP at P2y purinoceptors involved in relaxation of the guinea-pig isolated taenia coli (Burnstock et al, 1984) and in activation of the turkey erythrocyte phospholipase C (Boyer et al, 1989). On the other hand, ADP-fl-S was equipotent with ATP or ADP at P2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fur-thermore no correlation has been reported between the rate of breakdown of an agonist and its pharmacological potency at P2Y receptors (Welford et al, 1986). ADP-fl-S has been shown to be more potent than ATP or ADP at P2y purinoceptors involved in relaxation of the guinea-pig isolated taenia coli (Burnstock et al, 1984) and in activation of the turkey erythrocyte phospholipase C (Boyer et al, 1989). On the other hand, ADP-fl-S was equipotent with ATP or ADP at P2.…”
Section: Discussionmentioning
confidence: 99%
“…ADP analogues with modification on the terminal phosphate have been reported to be more effective (Burnstock et al, 1984) or selective (Hourani et al, 1988) P2Y receptor agonists. Furthermore, in contrast to 2-methylthio ATP, these ADP analogues are more resistant to ectonucleotidases than natural agonists (Welford et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Adenylyl 5′-(β,γ-methylene)-diphosphonate (β,γ-meATP) had much greater contractile effects on the guinea-pig bladder than ATP and the enantiomer of β,γ-meATP, L-β,γ-meATP, was even more potent, probably because L -β,γ-meATP was completely resistant to degradation [178], although it was inactive on P2Y receptors in the taenia coli [306]. Of the phosphorothioate analogues of ATP, ADP and AMP, it was found that adenosine 5′-O -1-thiotriphosphate, ATPβS, Rp-ATPβS and Sp-ATPβS were much more potent than ATP in the bladder [116]. Among the 2-methylthio derivatives of β,γ-meATP the potency order in the bladder was: difluoromethylene > methylene > dichloromethylene [179].…”
Section: P2x Receptors Mediating Contraction Of the Bladdermentioning
confidence: 99%
“…The effects of nucleotides were evident at concentrations above 0.3 1 M and did not reach a plateau at a concentration of 100 pM. This type of concentration/response curve has been observed for the activation of numerous cellular functions by purine and pyrimidine nucleotides [18,24,25,441. As nucleotide concentrations > 100 pM are unlikely to occur in the extracellular space in vivo [18,19,22,291, and as nucleotides at higher concentrations may permeabilize cells [45,461, the effects of higher concentrations of nucleotides were not investigated.…”
Section: Resultsmentioning
confidence: 98%
“…Purinoceptors can be divided into subtypes according to the effectiveness order of purinergic agonists [19,231. Phosphorothioate analogues of adenine nucleotides are useful tools to study the stereospecificity of purinoceptors [24,251. In addition to their direct effects on G proteins [lo,both GTP[yS] and GDP [PS] prevent activation of intact platelets via competitive antagonism with ADP at purinoceptors [26, 271. In addition to ATP, UTP modulates cellular functions.…”
mentioning
confidence: 99%